2015
DOI: 10.1071/hc15005
|View full text |Cite
|
Sign up to set email alerts
|

Estimated prevalence of hearing loss and provision of hearing services in Pacific Island nations

Abstract: INTRODUCTION:Hearing impairment (HI) affects an estimated 538 million people worldwide, with 80% of these living in developing countries. Untreated HI in childhood may lead to developmental delay and in adults results in social isolation, inability to find or maintain employment, and dependency. Early intervention and support programmes can significantly reduce the negative effects of HI.AIM: To estimate HI prevalence and identify available hearing services in some Pacific countries-Cook Islands, Fiji, Niue, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 11 publications
(21 reference statements)
1
20
0
Order By: Relevance
“…There is little research evidence on NIHS programs in the Pacific Islands [9]. Although this region is estimated to have among the highest global burden of childhood hearing loss, audiology services are virtually non-existent [10]. The United Nations Sustainable Development Goal Project has created opportunities to address childhood disability through WHO/UNICEF initiatives [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There is little research evidence on NIHS programs in the Pacific Islands [9]. Although this region is estimated to have among the highest global burden of childhood hearing loss, audiology services are virtually non-existent [10]. The United Nations Sustainable Development Goal Project has created opportunities to address childhood disability through WHO/UNICEF initiatives [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Early hearing detection programs are usually based on a biomedical model of health care, however, the development of paediatric audiology initiatives should also consider non-biomedical beliefs regarding childhood hearing impairment, as these may influence parental hearing health-care and health-seeking behaviour [7][8][9]. Audiology services are limited or non-existent in the Pacific Islands [10]. Yet, the World Health Organisation estimates that this region has among the highest global burden of hearing loss worldwide [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our lead study found an estimated prevalence of hearing impairment of about one in five people in a number of Pacific Island nations, with the majority of those affected being underserved. 1 The authors call for a collaborative effort between researchers and health professionals, as well as local organisations and Pacific Island nation governments, to develop the required services. In her guest editorial, Dr Shelly Chadha from the World Health Organization identifies the lack of population-based data on hearing loss, especially in low-income countries.…”
Section: T His Issue Of the Journal Of Primary Healthmentioning
confidence: 99%